Penerapan Model Learning Cycle 7E untuk Meningkatkan Hasil Belajar IPA Siswa di SMP Islam Terpadu Al-Kautsar - Mawarda, Asria (Lembaga Yasin AlSys, 2024)
This research aims to determine the science learning result of grade VIII students at SMP IT Al-Kautsar after implementing the Learning Cycle 7E model. This research was conducted at SMP IT Al-Kautsar in the 2023/2024 academic year. The research method used is Classroom Action Research (PTK) which consists of two cycles. In this research, the instrument used was a test instrument consisting of 8 descriptive questions. The data analysis technique used is descriptive analysis with data collection through observation sheets, interviews and written test instruments. Based on the research results, it can be seen that there is an increase in science learning outcomes by implementing the 7E learning cycle model for grade VIII students. This can be seen based on an increase in the percentage of student learning completeness in the first cycle from 45.65% to 93.47% in the second cycle. By implementing the Learning Cycle 7E learning model, it is possible to improve science learning outcomes for grade VIII students.